The Antihyperglycemic Activity of Sea Cucumber (Stichopushermanii) Ethanol Extract Against White Male Rats (Rattus novergicus) - R, Rahmadani; R, Rosidah; Jufri, Mahdi (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The purpose of this study was to determine antihyperglycemic activity of Sea Cucumber (Stichopushermanii) ethanol extract on white male rats, by observing changes in blood glucose levels after being induced by streptozotocin. Design:The research method used was experimental laboratory, where as test animals were divided into several groups given the test substance. The tests performed on animals were glucose tolerance test and antihyperglycemia test after being induced by streptozotosin. Interventions:Test animals that have been grouped into each group were given 0.5% Na CMC suspension as a negative control, metformin 65 mg / kg bw as a positive control, extracts of 50, 100, 200, 400 and 800 mg / kg bw as test samples. Main outcome measure:The results showed good results at a dose of 800 mg / kg bw in the 120th minute on the glucose tolerance test with blood glucose levels of 98.33 + 7.02, and the antihyperglycemic activity test after the rats were induced by streptozotocin with blood glucose levels of 65.84 + 2.93 on the 15th day. This value was not significantly different from the positive control (metformin) with a p value> 0.05. Conclusion:Ethanol extract of sea cucumber (Stichopushermanii) has antihyperglycemic activity at a dose of 800 mg / kg bw.